Mapping social enterprise models: some evidence from the "ICSEM" project. Issue 4 (6th November 2017) - Defourny, Jacques; Nyssens, Marthe
Abstract : Purpose: The purpose of this paper is to demonstrate that it is feasible to theoretically and empirically build an international typology of social enterprise (SE) models. The authors first rely on their previous work (Defourny and Nyssens, 2017), suggesting that the concept of "interest principles" can serve as a cornerstone in such perspective. This concept, when combined with that of SEs' "resource mixes", allows to design an analytical tool that shows from which "matrices" and through which "trajectories" several distinct SE models can emerge, namely, the "non-profit entrepreneurial model", the "social cooperative model", the "social business model" and the "public sector model". Design/methodology/approach: This paper combines deductive and inductive approaches. In a deductive perspective, the authors build upon the analytical framework proposed by Gui (1991) to identify capital interest, mutual interest and general interest as key driving forces and fundamental motives in the overall economy. To confront their theoretical construction and their tentative typology of SE models with field realities, the authors also adopt an inductive approach, relying on bottom-up research strategies developed in the seven "ICSEM country contributions" forming this special issue. Findings: At first view, mapping exercises of SE categories in the seven countries seem to highlight a high degree of heterogeneity. However, a closer analysis of these apparently diverging contributions clearly suggests that the four major SE models derived from the authors' theoretical framework find significant empirical support in most—if not all—countries. Originality/value: Although major statistical work to test the authors' typology of SE models remains to be carried out, mainly through the exploitation of the international ICSEM database (which covers over 700 SEs from more than 40 countries), this paper represents a first—although limited—attempt to collect empirical evidence for testing this typology.